A Planned Long Term Approach to Patient Management. (1st November 1990) - Binder, V
Abstract : On the basis of experience running an outpatient clinic for inflammatory bowel disease (IBO) for more than 25 years we concluded that a long term follow-up regimen offers both therapeutic and scientific advantages. The management program is based on treatment, information and social/ psychological support, factors which are mutually dependent. In Copenhagen County, patients arc offered lifelong affiliation with the IBD clinic, which means annual visits and easy access to treatment during recurrences. With this system, we have been able to conduct epidemiological studies on the incidence and prevalence of IBD in Copenhagen County. A systematic approach to clinical activity assessment is available during the course of the disease for the individual patients. We have found the economic and psychological costs for such a lifelong surveillance program in IBO to be more than outweighed by the benefits to patients and society.